2006
DOI: 10.1159/000091210
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Pharmacokinetics in Guinea Pig Inner Ear Perilymph

Abstract: Aim: To study the dexamethasone pharmacokinetics in the inner ear perilymph of guinea pigs using high-pressure liquid chromatography. Methods: Sixty-five guinea pigs were divided into three groups. In the first group, the drug application protocol used an intra-abdominal dose of 0.5% dexamethasone 4 mg·kg–1. In the second group, an intratympanic application dose of 0.5% dexamethasone 150 µl was used. The third group was the control group. The concentrations of dexamethasone in inner ear perilymph we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
(8 reference statements)
4
23
0
1
Order By: Relevance
“…In addition, these investigators found that based on plasma levels, intratympanic dexamethasone injections did not result in significant systemic absorption. Similar results were obtained by others measuring perilymph steroid concentrations following systemic versus local administration [59,60]. Collectively, these pharmacokinetic studies show that the limited permeability of the blood–labyrinth barrier prevents systemic absorption of medications delivered to the inner ear by intratympanic injections and that the unique properties of the round window can be exploited for effective targeted drug delivery to the inner ear.…”
Section: Intratympanic Therapysupporting
confidence: 84%
“…In addition, these investigators found that based on plasma levels, intratympanic dexamethasone injections did not result in significant systemic absorption. Similar results were obtained by others measuring perilymph steroid concentrations following systemic versus local administration [59,60]. Collectively, these pharmacokinetic studies show that the limited permeability of the blood–labyrinth barrier prevents systemic absorption of medications delivered to the inner ear by intratympanic injections and that the unique properties of the round window can be exploited for effective targeted drug delivery to the inner ear.…”
Section: Intratympanic Therapysupporting
confidence: 84%
“…There have been numerous pharmacokinetic studies of locally-applied corticosteroids in animals (Nomura 1984;Parnes et al 1999;Chandrasekhar et al 2000;Bachmann et al 2001;Hahn et al 2006Hahn et al , 2012Liu et al 2006;Plontke et al 2008b;Yang et al 2008;Wang et al 2009;Borden et al 2011;Salt et al 2011a) and humans (Bird et al 2007;Bird et al 2011), but only a subset of these studies has been analyzed quantitatively to derive an elimination rate. Plontke and analyzed prednisoline data of Bachmann et al (2001) from guinea pigs and found it to be consistent with an elimination half-time from perilymph of 130 min.…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms are based on the current knowledge of inner ear fluid dynamics and aim at developing reliable prediction from animal studies. Other investigators have used more traditional approaches by performing pharmacokinetic studies in rodents [Chandrasekhar et al, 2000;Chen et al, 2006;Liu et al, 2006;Paulson et al, 2008;Wang et al, 2009]. These studies, while interesting, are of limited value with regard to projecting the inner ear disposition of drug substances in humans.…”
Section: Introductionmentioning
confidence: 99%